السلطة التقديرية للقاضي في نطاق انعقاد العقد وصحته - د. عبد السلام عبد الجليل سالم, (مجلة أبحاث قانونية, 2023)
تناولت هذه الدراسة موضوعًا ذا أهمية قانونية بالغة، وهو السلطة التقديرية للقاضي، والتي هي ولا شك من السعة والشمول بحيث لا يمكن ادراكها في كتاب أو بحث واحد، لذا انصبت الدراسة على السلطان التقديري للقاضي المدني بشكل اكثر تحديدا يقصرها على السلطة التقديرية للقاضي في نطاق العقد باعتباره المصدر الأصيل للالتزام، ولما يفرضه القانون من حماية على غلو وعسف الإرادة الناظمة لهذا العقد. ولدواعي التخصيص ونزولا عند مقتضيات التفاصيل الجديرة بالبحث والدراسة، فقد اقتصر البحث على دراسة السلطة التقديرية للقاضي المدني في مرحلة انعقاد، وتقدير شروط صحته، مستعينين في ذلك بعرض مسلك التطبيقات القضائية وتعقب آراء الفقه والباحثين فالموضوع، مع بيان وافي لمفهوم السلطة التقديرية للقاضي المدني كتمهيد للبحث في هذا الموضوع. Abstract This study addressed a very important legal topic which is the Discretionary Authority of the Civil Judge, which is undoubtedly so broad and comprehensive that it can't be apprehend in one single book or research. Therefore, the study focused on the discretionary power of the civil Judge, more specifically limiting it to the discretionary power of the judge within the scope of the contract as the original source of obligation and the protection imposed by law on the excess and arbitrariness of the volition regulating this contract. for reasons of specification and specialization and down to the requirements of details worthy research and study, the research was limited to studying of the discretionary authority of the civil judge in a convening stage and estimating the condition of its validity using the presentation of course judicial provisions and trace the views of jurisprudence and researchers on the subjects with an adequate explanation of the concept of the Discretionary of Civil Judge as prelude to research on this topic